Historical, current and future distribution of Cedrela odorata in Mexico - Hernández Ramos, Jonathan; Reynoso Santos, Roberto; Hernández Ramos, Adrian; García Cuevas, Xavier; Hernández-Máximo, Edgar; Cob Uicab, José Vidal; Sumano López, Dante (Instituto de Ecología, A.C., 2018)
Background and Aims: Tropical forests play an indispensable role to confront and reduce environmental degradation. The objective of this work was to determine, through ecological niche simulation models, the historical and current distribution of Cedrela odorata in Mexico.Methods: A base of 1747 presence data of C. odorata was used. For the modeling 19 climatic-environmental variables were used, as well as the layers of altitude, orientation, slope and soil type. The ecological niche modeling was carried out in the program MaxEnt, with 75% of the sample for training and the Logistic, Cumulative, Raw and Cloglog models. The validation was carried out with 25% of the sample and the Crossvalidate technique.Key results: The use of the Cloglog regression is the one that most adheres to the potential distribution for the species, otherwise using the Raw type modeling, since the projection of the potential area is very restrictive and compact, followed by the Cumulative regression and the Logistic regression, being these an intermediate point for the modeling of the historical distribution of C. odorata in Mexico.Conclusions: The historical distribution obtained from this model showed that the species has very high values of probability in the southern part of the Yucatán Península, north and south of Chiapas and the coastal plain of the Gulf in the Veracruz state with respect to the current distribution reported. This suggests a reduction in the distribution of the species in the country.